Determination of Babesia canis and Ehrlichia canis, in hemolymph of teleogynous ticks of Riphicephalus sanguineus (Revista Sistemas de Producción Agroecológicos, 2013)
The present study was carried out in the laboratory of microbiology at the University of the Llanos Orientales, located 4 km from the city of Villavicencio (Meta), with an average temperature of 28°C, relative humidity of 80% and a height of 440 m.a.s.l. The objective was to determine the presence of Babesia canis and Ehrlichia canis, through extended and Giemsa in the hemolymph of engorged females of Rhipicephalus sanguineus ticks (RS) by dogs captured in the city of Villavicencio, using the proposed identification technique by Lopez (1980) in order to determine whether the technique is applicable to this tick. For the study collected 200 ticks engorged RS, which were taken from infected canines in the city of Villavicencio. For hemolymph-examination ticks were washed with water and 70% rubbing alcohol, then were dried with paper towel petri dishes fitting them in to place to incubate at 28°C and 80% relative humidity for three days. He proceeded to cut the shanks carefully each incubation ticks, extracting from them a sample of hemolymph. This drop of hemolymph was placed on slide slides, fixed with methyl alcohol for 2 minutes, then began staining with Giemsa for 45 minutes, then observed under a microscope (100x) and cells were identified by the hemolymph. The samples of hemolymph RS, yielded a negative result of 100% for both study pathogens Babesia canis and Ehrlichia canis. Although not determined the presence of Ehrlichia canis and Babesia canis in hemolymph smears taken from the tarsus of the RS engorged in the samples taken cannot be assumed that blood parasites are not present in canines, for this reason it is advisable to perform sampling of ticks in different phases of the life cycle, based on studies in the hemolymph of RS varying the temperature. We conclude that the technique described by Lopez in 1980, does not apply to the determination of Babesia canis and Ehrlicha canis in the conditions developed in the present work.
Keywords: hemoparasite; Babesia canis; Ehrlichia canis; Riphicephalus sanguineus